Leadership soft skills that affect organizational climate of district health offices in Khon Kaen, Thailand - Wongkalasin, Khemakorn; Bouphan, Prachak; Ngang, Tang Keow (Asia-Pacific Journal of Science and Technology, 2017)
This cross-sectional survey research aimed to study leadership soft skills that affect organizational climate of district health offices in Khon Kaen province, Thailand. Two research instruments were a self-administered questionnaire and an in-depth interview guideline. The Cronbach’s alpha reliability coefficient of the questionnaire ranges from 0.88 to 0.96. After approved for ethical review, the data collection took place in late 2012 and early 2013. Out of 144 questionnaires distributed, a total of 121 questionnaires were valid for data analysis (response rate = 84.03%). Eight key informants were then appointed for interview. Descriptive statistics, Pearson’s correlation, and stepwise multiple linear regression were performed for quantitative data analysis. The findings from the in-depth interview were evaluated by content analysis approach. The findings revealed that the level of leadership soft skills employed by district health officers is high (4.10?0.50). Likewise, the level of organizational climate was high (3.89?0.46). There was moderate positive relationship between leadership soft skills and organizational climate at significant level (r = 0.569, p-value < 0.001). Two leadership soft skills; personal mastery and planning & organizing, were significant predictors towards organizational climate (r2 = 0.321, p-value < 0.001). The findings from the in-depth interview suggested that district health officers should pay attention on the dynamic of organizational climate. Additionally, leadership soft skills development can be done through practices.